Citarum plastic exploration for Solusi Sungai Resik's community environmental fundraising action - Vita Jasinta Sarjono; Sanabila Fatah; Terbit Setya Pambudi; Hanif Azhar (Universitas Muhammadiyah Malang, 2025)
This study responds to the growing environmental problem of plastic pollution in the Citarum River and to the limited funding available to local environmental organizations. It aims to identify the most suitable material from a blend of recycled plastics—LDPE and HDPE—to serve as the base material for fundraising bracelets for the Solusi Sungai Resik Foundation. The material selection is based on its availability at the foundation's waste management facility and the quality of the processed outcome for bracelet production. The research employs an adapted Material Development Design (MDD) method, which includes material exploration, sample creation, durability testing, and user interviews to assess material experience through aesthetic, tactile, emotional, and functional aspects. The adaptation of MDD in this study focuses on selecting and validating material experience, without fully implementing it in the final product, due to technical constraints. The results show that the LDPE-HDPE blend produces a visually appealing marble pattern resembling river streams, has a comfortable texture, and elicits positive emotional responses from informants. The material also demonstrates resistance to water, sunlight, and skincare products, and is safe for skin contact. These findings indicate that plastic waste from the Citarum River can be transformed into a functional and meaningful material for fundraising bracelets supporting Solusi Sungai Resik's environmental mission. Beyond material innovation, this approach contributes to social change by raising environmental awareness, encouraging public participation, and supporting the financial sustainability of local environmental initiatives. Penelitian ini merespons permasalahan lingkungan yang semakin meningkat terkait pencemaran plastik di Sungai Citarum serta keterbatasan pendanaan yang dihadapi oleh organisasi lingkungan lokal. Penelitian ini bertujuan untuk mengidentifikasi material paling tepat dari campuran plastik daur ulang, yaitu LDPE dan HDPE, yang akan digunakan sebagai bahan dasar gelang penggalangan dana untuk Yayasan Solusi Sungai Resik. Pemilihan material didasarkan pada ketersediaannya di fasilitas pengelolaan limbah yayasan serta kualitas hasil olahan untuk produksi gelang. Penelitian ini menggunakan metode Material Development Design (MDD) yang telah disesuaikan, meliputi eksplorasi material, pembuatan sampel, pengujian daya tahan, dan wawancara pengguna untuk menilai pengalaman material dari aspek estetika, taktil, emosional, dan fungsional. Adaptasi MDD dalam penelitian ini difokuskan pada pemilihan dan validasi pengalaman material tanpa penerapan penuh pada bentuk produk akhir karena keterbatasan teknis. Hasil penelitian menunjukkan bahwa campuran LDPE-HDPE menghasilkan pola marmer yang menarik secara visual menyerupai aliran sungai, memiliki tekstur yang nyaman, dan memicu respons emosional positif dari para informan. Material ini juga tahan terhadap air, sinar matahari, produk perawatan kulit, serta aman bersentuhan dengan kulit. Temuan ini menunjukkan bahwa limbah plastik dari Sungai Citarum dapat diubah menjadi material fungsional dan bermakna untuk gelang penggalangan dana yang mendukung misi lingkungan Solusi Sungai Resik. Selain inovasi material, pendekatan ini berkontribusi pada perubahan sosial melalui peningkatan kesadaran lingkungan, mendorong partisipasi publik, dan mendukung keberlanjutan pendanaan bagi inisiatif lingkungan lokal.